Canines as a measuring tool for leaf tent construction in Dermanura watsoni - Villalobos Chaves, David (2013)
Many animals are capable of constructing structures to modify the environment for their own benefit. The design of these structures requires animals to perceive dimensions. However, how animals take measurements to achieve the final design of the structures they construct is known for only very few species. In the Neotropics, a few bat species build roosts or leaf tents that serve different purposes. Thomas’s fruit-eating bat (Dermanura watsoni) constructs tents that have complex designs, when compared to other tent building bats. The bifid tent is a design built by producing a long, J-shaped cut on each side of understory plant leaves. We expect that to accomplish this complex design bats would require precise measurements during tent construction. We measured several bat morphological traits to infer which of them, if any, was used by the bats as a measuring device. Dermanura watsoni uses the distance between their lower canines to increase the perpendicular distance of the J-cut to the central vein of the leaf along the J-cut. The bat adds the distance between the canines to each subsequent secondary vein cut. This is the first study to infer which body part D. watsoni most likely uses as a measuring tool. Our results provide new insight into the evolution of body parts as measuring devices during tent construction in related and unrelated tent-building bat species.